In vivo microscopic and optical coherence tomography classification of neurotrophic keratopathy. Issue 5 (21st September 2018) - Mastropasqua, Leonardo; Nubile, Mario; Lanzini, Manuela; Calienno, Roberta; Dua, Harminder S.
Abstract: Neurotrophic keratopathy (NK) is a rare degenerative corneal disorder characterized by instability of epithelial integrity with consequent epithelial defects that can worsen up to persistent epithelial defects with stromal melting and ulceration. The pathogenesis of NK springs from a variable degree of damage to the trigeminal nerve plexus, leading to a reduction or total loss of corneal sensitivity. Mackie classification (1995) distinguishes three stages of NK, based on the severity of clinical presentation. The technological innovations in corneal diagnostic imaging allow clinicians to accurately study the morphometry and morphology of corneal structure with microscopic resolution. In this study, 45 patients affected by NK at different stages underwent in vivo confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS‐OCT) with particular attention to analyze subbasal nerve plexus fibers and the stromal structure. At the light of IVCM and AS‐OCT observations, we propose a different staging of NK with respect to the Mackie's classification that takes into account the severity of subbasal nerve fibers damage and the extension in depth of stromal ulceration; this classification better defines, at the time of diagnosis, the cellular and structural alterations in the affected corneas, with possible prognostic and therapeutic values in the management of NK. Abstract : In vivo confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS‐OCT) are diagnostic devices useful to analyze neurotrophic keratopathy (NK). Based on the IVCM and AS‐OCT results, a new classification of NK can be proposed. According to this classification, important information about prognosis, follow‐up, and therapeutic approach can be achieved